Methodology for design of suitable dishes for dysphagic people. (August 2020) - Merino, Gorka; Gómez, Inmaculada; Marín-Arroyo, M. Remedios; Beriain, María José; Ibañez, Francisco C.
Abstract: A methodology to adapt dishes for cerebral palsy (CP) dysphagic people was developed. Five conventional dishes were cooked, blended and texturized with mixtures of thickeners and gelling agents based on xanthan gum. The most appropriate texturizing agents were selected, the textural thermostability of the dishes was studied, and the shelf-life was evaluated by back extrusion, sensory and microbiology analysis. Information about the acceptability of the adapted dishes by CP dysphagic people was obtained through the control of the consumed fraction and the liking or disliking reaction after eating the dishes. The adapted dishes considered suitable for swallowing process showed maximum force between 6.2(0.1) N and 18.9(3.3) N, minimum force between −3.9(0.3) N and −9.2(1.3) N, and Fmin /Fmax ratio between 0.4(0.0) and 0.7(0.0). Regarding sensory characteristics, the adapted dishes showed low stickiness, residue and firmness, and high suitable texture score. The methodology was appropriate for developing suitable dishes, sensorially accepted by dysphagic people, thermostable for 7 days refrigerated storage and ready-to-eat. Industrial relevance: This study presents the technological basis for the standardized design of suitable ready-to-eat dishes for dysphagic people. The methodology developed is of great interest to the industry of ready-to-eat dishes. Highlights: A method to adapt conventional dishes for dysphagic people was developed. Acceptability of adapted dishes was evaluated by cerebral palsy dysphagic people. Sensory analysis was fundamental in the selection of texturizing agents. Instrumental and sensory texture analyses were useful to study the thermostability. Mixtures of xanthan-based additives led to suitable and stable dishes.